Genome assembly of the cichlid fish Astatotilapia latifasciata with focus in population genomics of B chromosome polymorphism - Jehangir, Maryam [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
B chromosomes (Bs) are additional to the standard regular chromosome set (As), and present in all groups of eukaryotes. A reference genome is key to understand genomics aspects of an organism. Here, we present the de novo genome assembly of the cichlid fish A. latifasciata: a well known model to study Bs. The assembly of A. latifasciata genome has not been performed so far. The main focus of this study is to analyze and assemble the A. latifasciata genome with no B (B-) and with B (B+) chromosomes. The assembled draft B- and B+ genomes comprised of 774 Mb and 781 Mb with 1.8 Mb and 2.5Mb of N50 value of scaffolds respectively, and spanning 23,391 number of genes. High coverage data with Illumina sequencing was obtained for males and females with 0B, 1B and 2B chromosomes to provide information regarding the population polymorphism of these genomes. We observed a high scale genomic diversity in all analyzed genomes showing a high rate/frequency of population polymorphism with no evident effect of B chromosome presence. However, the B specific single nucleotide polymorphisms were found in the sequences that were located on B chromosome. While, the whole-genome rearrangements (inter chromosomal translocations) were detected in B+ genome, and structural variations including insertions, deletions, inversions and duplications were predicted in a representative genomic region of B chromosome. These results bring an evidence that existence of Bs in a genome should favour the accumulations of mutations and structural polymorphisms in the amlified genomic regions present on B chromosmes. In addition, we also performed the coverage based sequence study coupled with FISH mapping which revealed: 1) the existence of high copy number of inactive Indian Hedgehog b (Ihhb) gene on B chromosome emerging as a pseudogene after series of duplication events ultimately becoming a major structural component of B; 2) B chromosome have incorporated the entire 45S RNA cluster (18S ribosomal RNA, internal transcribed spacer 1, 5.8S ribosomal RNA, internal transcribed spacer 2, and 28S ribosomal RNA) from the A complement set. The assembly of A. latifasciata genome will serve as a reference for genetic analysis and the approach presented in this paper opens the perspective to advance understanding B chromosomes biology.
Montagem de genoma do peixe cíclido Astatotilapia latifasciata com foco em genômica populacional de polimorfismo cromossomo B
Keywords: Genome Assembly; Cichlid fish; B chromosome; Genome; Sequencing; Polymorphism; Evolution